PERANCANGAN SISTEM INFORMASI NILAI MURID BERBASIS WEBSITE PADA SMA PELITA KASIH - Fernandes, Jordan; Wasino (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
The development of science and technology is increasingly rapid in the field of information technology such as internet technology. In the education sector in Indonesia, almost all tertiary institutions are quite familiar with and make good use of internet technology. Such as services to find out information on tuition fees, grades, and so on. At the level of high school education (SMA). Not many schools are well acquainted with the benefits of this internet technology. One of them is SMA Pelita Kasih, this technology is only used as an additional facility to display simple information. This technology has not been utilized as the main media database, one of which is a valuable. Value data processing is still done manually, this process is considered quite slow and requires precision to maintain the accuracy of the data. Therefore it is necessary to develop a system to streamline time and maintain data confidentiality. In developing this system, the stages used were from the Development System Development Life Cycle (SDLC), namely, Planning, Analysis, Design, Programming, Testing, Operation, and Maintenance. While the programming language used by the author is XAMPP and Sublime Text 3.